Analysis of Computer Network Performance on Communication and Informatics Office of West Sumbawa Regency Using Quality of Service Method - Sabri Balafif; Ikhda Qurrata Aini (Journal of Information System and Informatics, 2022)
This study aims to determine and analyze network performance with quality of service parameters in realizing good and optimal network performance quality so that it can be adjusted between the efficiency of network needs and the effectiveness of user access at the Communication and Informatics Office of West Sumbawa Regency. The process of accumulating data is obtained by measuring the quality of service parameters using the quality of service method and measuring bandwidth load distribution with the load set at 30 Mbps. The quality of service method on the network, the influence between the variables of network performance quality on the internet connection, and the bandwidth capacity of each user are known. The study results from the quality of service analysis at the Communication and Informatics Service of West Sumbawa Regency entered the excellent category with an average throughput value ranging from 10,320-1,026,454 kbps from the fourth index being in the excellent category. The average packet loss value of 0-1.5% of the third index is in a good category, with the highest value occurring on the fifth day, 1.5%. The average delay value ranges from 7-150 ms, with the highest delay value occurring on the first day due to the user's distance from the remote network access source and queues in dense packet transmission. The average jitter value of 1-12 ms from the third index is in a good category, and the maximum result of the bandwidth value set in size is 9,092,407 bps